23.4% Sodium Chloride Versus Mannitol for the Reduction of Intracranial Pressure in Patients With Traumatic Brain Injury: A Single-Center Retrospective Cohort Study. Issue 8 (August 2021) - Tatro, Hayley A.; McMillen, James C.; Hamilton, Leslie A.; Rowe, A. Shaun
Background: Intermittent doses of mannitol or hypertonic saline are recommended to treat elevated intracranial pressure (ICP). However, it is unclear if one agent is more effective than the other. Previous studies have compared mannitol and hypertonic saline in reduction of ICP, with conflicting results. However, no study thus far has compared 23.4% sodium chloride with mannitol. Objective: The objective of this study was to determine the difference in absolute reduction of ICP 60 minutes after infusion of 23.4% sodium chloride versus mannitol. Methods: This was a single-center retrospective cohort study that included patients at least 16 years old admitted to the trauma/surgical intensive care unit between August 8, 2016, and August 30, 2018, who received either 23.4% sodium chloride 30 mL and/or mannitol 0.5 g/kg and had an ICP monitor or external ventricular drain in place. The primary outcome was absolute reduction in ICP 60 minutes after infusion of hyperosmolar therapy. Results: In all, 31 patients and 162 doses of hyperosmolar therapy were included in the analysis. There was no statistically significant difference in the primary end point of absolute reduction of ICP 60 minutes after infusion of hyperosmolar therapy comparing 23.4% sodium chloride 30 mL with 0.5 g/kg mannitol ( P = 0.2929). There was no statistically significant difference found for any secondary end points. Conclusion and Relevance: No difference was found for absolute reduction of ICP at 30, 60, and 120 minutes, respectively, after infusion of hyperosmolar agent or time to next elevated ICP. Patient-specific parameters should be used to guide the choice of hyperosmolar agent to be administered.